CRIMINAL THREATS FOR PERPETRATORS OF OMISSION IN CHILD ABUSE IN INDONESIA - Lina Dwi Istiqomah; Nyoman Serikat Putra Jaya; Duwi Aryadi (UNISSULA, 2019)
Child abuse is increasingly happening every day. Even cases of child abuse are mostly perpetrated by parents. Many people who know, but those who do know just tend to leave and seem unconcerned because of the notion that violence is not their problem. There is also an assumption that violence against children is one of the methods of education given by parents to children. So it is not right for other parties to interfere in the problem of educating children. The existence of these assumptions makes people become indifferent and allow violence. The problem is there is a criminal threat for those who allow child abuse. In this article, the normative legal approach is to use literature or literature studies and qualitative descriptive analysis of the problem. This research shows the ignorance of the public regarding the threat of crime because of acts of omitting violence against children which is known to make child violence increase and have a greater impact in the future. Regarding the omission of violence against children itself has been regulated in Article 78 of the Child Protection Act, whereby anyone who does not allow violence against children can be subject to criminal threats.